PHYSICO-CHEMICAL, PROXIMATE COMPOSITION, ASCORBIC ACID, SENSORY, AND MICROBIOLOGICAL QUALITY OF MINIMALLY PROCESSED CARICA PAPAYA CONSUMED IN RIVERS STATE, NIGERIA - PC, OBINNA-ECHEM; LI, BARBER; F, OWUNO (Innovare Journal of Food Sciences, 2020)
Objective: This study evaluated the physico-chemical, proximate, ascorbic acid, sensory, and microbiological properties of minimally processed Carica papaya consumed in Rivers State Nigeria. Methods: Minimally processed papaya in transparent polyethylene bags were purchased from four different locations: Nwinpi, Mile III, Rumuokuta, and Rumuokoro Junctions in Port Harcourt, Rivers State, Nigeria. Control sample was prepared in the laboratory. Standard analytical methods were used for analysis. Results: pH and titratable acidity ranged from 4.90–5.20 to 1.00–1.04% citric acid, respectively. Moisture, fat, ash, crude fiber, and carbohydrate ranged, respectively, from 85.80–89.60, 0.64–0.69, 0.55–0.96, 1.71–1.93, and 7.20–10.97%. Energy value was 35.31–50.07 kcal/g while protein was 0.09% for all samples. Ascorbic acid varied significantly (p<0.05) from 17.81 to 44.91 mg/100 g. Sensory results showed that 75% of the assessors’ degree of likeness for aroma, appearance/color, texture (smoothness), sweetness, and overall acceptability was that of moderate to extreme likeness. Total aerobic, coliform, Escherichia coli, Salmonella, and Staphylococcus aureus counts varied from 3.85–5.76, 3.74–5.68, 3.95–5.57, 3.82–5.58, and 3.30–5.45 Log10CFU/g, respectively. The control had significantly (p<0.05) the least bacterial count. Fungi count varied from 3.65 to 4.62 Log10CFU/g. Conclusion: The minimally processed papaya was low in acidity, rich in ascorbic acid and a good source of the nutrient. Sensory attributes of the products were acceptable to the assessors. Microbial counts were unsatisfactory and can pose a risk factor to public health.